The Choice of Dry Eye Therapy Depending on Ocular Surface Condition - S. V. Yanchenko; A. V. Malyshev; S. N. Sakhnov (Oftalʹmologiâ, 2021)
Purpose: to develop approaches to differentiated substitution therapy in patients with dry eye (DE) of mild and moderate severity.Patients and methods. We examined 86 DE patients (22–45 years old; 38 men, 48 women). Group-1 included 54 patients (54 eyes) with mild DE under conditions of combined lipid-mucose-deficiency, group-2 32 patients (32 eyes) with moderate DE against the background of combined lipid-aqua-mucose-deficiency. Conducted: DE symptoms registration (OSDI scale); Norn and Shirmer-1 tests; OCT meniscometry; assessment of the Bijsterveld xerosis index and ‘lid-vipers’ symptom identification; Norn’s compression test. To assessment the therapy effectiveness, patients in both groups were divided into subgroups. Patients of subgroup 1.1 (18 eyes) carried out ‘fat-water’ type emulsion instillations, subgroup 1.2 (18 eyes) — 0.15 % sodium hyaluronate instillation (Hylabak®), subgroup 1.3 (18 eyes) — 3.0 % trehalose (Thealoz®) — 1–2 drops, 4 times a day. All persons included in group-1 were additionally recommended to apply 5.0 % dexpanthenol gel at night. Patients of subgroup 2.1 (16 eyes) received 0.15 % sodium hyaluronate instillation (Hylabak®), patients of subgroup 2.2 (16 eyes) 0.15 % sodium hyaluronate (Hylabak®) and 3.0 % trehalose (Thealoz®) instillation — 4 times a day. All patients included in group-2 were additionally recommended to apply ointment with vitamin A at night. The main criterion for the therapy effectiveness was the tear film brake up time (TBUT, s) two months after the start treatment. Statistical processing included: calculation the mean and its standard deviation (M ± s); assessment of the significance of differences (Wilcoxon’s t-test, KruskalWallis test, Mann-Whitney U-test).Results. In group-1 patients the following TBUT dynamics was recorded: in subgroup 1.1 — from 5.4 ± 0.5 to 6.2 ± 0.6 s (p < 0.05); in subgroup 1.2 — from 5.2 ± 0.4 to 6.6 ± 0.6 s (p < 0.05); in subgroup 1.3 — from 5.3 ± 0.5 to 7.1 ± 0.7 s (p < 0.05). The most pronounced TBUT increase was noted in subgroup 1.3 (trehalose instillation). In group-2, the increase in TBUT was: in subgroup 2.1 — from 3.5 ± 0.3 to 4.7 ± 0.3 s (p < 0.05); in subgroup 2.2 — from 3.4 ± 0.2 to 5.2 ± 0.4 s (p < 0.05). A significantly more pronounced TBUT increase was noted in subgroup 2.2 (sodium hyaluronate and trehalose instillation).Conclusion. In our opinion, differentiated approaches to DE replacement therapy may be included: for mild DE in conditions of lipid-mucose-deficiency — instillation of bioprotector based on 3.0 % trehalose (Thealose®); in case of moderate DE against the background of lipid-aqua-mucose-deficiency — 0.15 % sodium hyaluronate (Hylabak®) instillation in combination with a bioprotector based on 3.0 % trehalose (Thealoz®).